Monthly or Weekly Supplementation with Cholecalciferol 20,000 IU in People Living with HIV: Results from a Nested Cohort Study - Sebastian Noe; Christine I. Moeckel; Christiane Schwerdtfeger; Celia Oldenbuettel; Hans Jaeger; Eva Wolf; Christoph D. Spinner (Interdisciplinary Perspectives on Infectious Diseases)
Background. There is still considerable uncertainty in handling vitamin D deficiency in people living with HIV (PLWH), due to a lack of comparative data and the wide range of recommended daily intake. Nondaily supplementation might be preferred in many PLWH, but recommendation on dosing has not been established. We aimed to compare the efficacy of weekly versus monthly supplementation with cholecalciferol 20,000 IU in a group of PLWH with vitamin D deficiency in Western Europe. Study Design. Longitudinal, retrospective nested cohort study of PLWH from two large clinical care centers in Munich, Germany. Results. Of 307 patients with vitamin D deficiency, 124 patients received vitamin D supplementation (weekly supplementation in 84 (67.7%)). 46.4% and 22.5% of patients achieved 25(OH)D levels ≥30 ng/mL after 12 months of weekly and monthly supplementation with cholecalciferol 20,000 IU, respectively (p=0.011). Dosing interval as well as 25(OH)D baseline levels >15 ng/mL were associated with the normalization of 25(OH)D. Conclusion. A higher rate of 25(OH)D level normalization can be achieved via weekly supplementation. For several PLWH, even a weekly dose of cholecalciferol 20,000 IU might not be adequate to maintain 25(OH)D levels >30 ng/mL without an initial “loading” dose. The response to supplementation is poorly predictable at an individual level.